Polska muzyka rockowa w „Nowej Wsi” - Chełminiak, Patrycja (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article presents the subject of rock music explored in the newspaper “Nowa Wieś”, which was published in the years 1948–2000. While doing research on “Nowa Wieś”, I noticed that it is not a popular source material in historical studies, and I have not met with a situation in which the subject concerning Polish rock music was analysed on the basis of “Nowa Wieś”. The newspaper was aimed at young people from the rural environment and it was initiated by ZMP (Polish Youth Union). The features in “Nowa Wieś” were not only about political and agricultural issues, but also about typical topics for young people like love and music. Rock music was something new both in the USA and in Europe, although it was created from various musical trends such as rock & roll and jazz. At that time, Poland was ruled by the Communists and the press was also controlled by them. The article focuses on Polish rock music in the last decades of the twentieth century referring to well-known bands, artists, songs, musical events,and musical styles. The subject is so vast that I only show some examples of it, and each of them is analysed as it was presented in the newspaper. The most popular journalist who used to write articles for “Nowa Wieś” was Jerzy J. Kaczmarek so I have chosen mainly his texts to work on the subject. Rock music itself is still popular. Even many old songs are known nowadays. It is constantly changing, and we can see how and why these changes are taking place. “Nowa Wieś” has showed me an unknown view of Polish rock music from the perspective of the newspaper issued to a particular reader in the Communist times.